1993
DOI: 10.1182/blood.v81.9.2321.2321
|View full text |Cite
|
Sign up to set email alerts
|

Echicetin: a snake venom protein that inhibits binding of von Willebrand factor and alboaggregins to platelet glycoprotein Ib

Abstract: Echicetin, a new protein isolated from Echis carinatus venom by reverse phase and ion exchange chromatography specifically inhibited agglutination of fixed platelets induced by several platelet glycoprotein Ib (GPIb) agonists, such as bovine von Willebrand factor (vWF), alboaggregins, and human vWF in the presence of botrocetin. Unlike alboaggregins, echicetin bound to GPIb but did not induce agglutination of washed or fixed platelets. In contrast to disintegrins, it did not block adenosine 5'-diphosphate (ADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 31 publications
6
59
0
Order By: Relevance
“…In contrast to crotalin, intravenous administration of agkistin reduced platelet counts (Figure 7). However, this result is consistent with the previous reports that echicetin and jajaraca GPIb‐BP caused transient thrombocytopenia in mice ( Peng et al ., 1993 ; Fujimura et a ., 1995 ). At present, the tendency of these GPIb antagonists in causing thrombocytopenia is a precaution to be taken, however, the exact mechanism remains to be investigated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast to crotalin, intravenous administration of agkistin reduced platelet counts (Figure 7). However, this result is consistent with the previous reports that echicetin and jajaraca GPIb‐BP caused transient thrombocytopenia in mice ( Peng et al ., 1993 ; Fujimura et a ., 1995 ). At present, the tendency of these GPIb antagonists in causing thrombocytopenia is a precaution to be taken, however, the exact mechanism remains to be investigated.…”
Section: Discussionsupporting
confidence: 93%
“…The protein standards used in order of decreasing molecular mass were phosphorylase b (97 kDa), bovine serum albumin (66.2 kDa) ovalbumin (45 kDa), bovine carbonic anhydrase (31 kDa), soybean trypsin inhibitor (21.5 kDa) and lysozyme (14 kDa). (B) N‐terminal amino acid sequences of the α‐ and β‐subunits of agkistin compared to those of other reported GPIb‐binding proteins including echicetin ( Peng et al ., 1993 ), agkicetin ( Chen & Tsai, 1995 ) and tokaracetin ( Kawasaki et al ., 1995 ). Single‐letter amino acid code was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysteine-rich secretory protein is a single-chain bioactive polypeptide identified in several organisms, including snakes [40], reptiles [41], and mammals [42]. Snake venom cysteine-rich secretory protein can block smooth muscle contraction by blocking l-type calcium channels [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, it also induces the agglutination of fixed human platelets without the need for any cofactor. These authors later reported that echicetin, purified from the venom of Echis carinatus, inhibits the binding of AL-B and vWF to GPIb without inducing platelet agglutination [13]. However, the effects of echicetin on h-SIPA and its N-terminal amino acid sequence have not been reported.…”
Section: Introductionmentioning
confidence: 99%